(untitled) (Eurasian Journal of Engineering and Technology, 2024)
This article provides an overview of modern methods for increasing the reliability of fiber-optic information transmission systems. The study of reliability is an important aspect in the development of telecommunication networks, especially in the context of the growing demand for high-speed and continuous data transmission. The article examines various techniques and approaches, including improvements to physical infrastructure, monitoring and control techniques, and the use of advanced error detection and correction algorithms.